2013
DOI: 10.1371/journal.pgen.1003926
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping the Genetic Association of the Major Histocompatibility Complex in Multiple Sclerosis: HLA and Non-HLA Effects

Abstract: The major histocompatibility complex (MHC) region is strongly associated with multiple sclerosis (MS) susceptibility. HLA-DRB1*15:01 has the strongest effect, and several other alleles have been reported at different levels of validation. Using SNP data from genome-wide studies, we imputed and tested classical alleles and amino acid polymorphisms in 8 classical human leukocyte antigen (HLA) genes in 5,091 cases and 9,595 controls. We identified 11 statistically independent effects overall: 6 HLA-DRB1 and one D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
247
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 272 publications
(272 citation statements)
references
References 47 publications
19
247
1
5
Order By: Relevance
“…This resulted not only in the description of multiple class II HLA‐DRB1 and HLA‐DRQ1 classical alleles imputed from SNP genotypes, but also epistatic interactions between HLA‐DQA1*01:01 and HLA‐DRB1*15:01 and between HLA‐DQB1*03:01 and HLA‐DQB1*03:02. These results raise certain functional questions, for example why the protective effect of HLA‐DQA1*01:01 only manifests in the presence of the HLA‐DRB1*15:01 risk allele 50, 51. Several variants outside the classical regions of the MHC (both class I and class II) were also shown to be independently associated, suggesting biological functions beyond antigen display underlie the MHC risk effects.…”
Section: The Role Of the Mhcmentioning
confidence: 98%
“…This resulted not only in the description of multiple class II HLA‐DRB1 and HLA‐DRQ1 classical alleles imputed from SNP genotypes, but also epistatic interactions between HLA‐DQA1*01:01 and HLA‐DRB1*15:01 and between HLA‐DQB1*03:01 and HLA‐DQB1*03:02. These results raise certain functional questions, for example why the protective effect of HLA‐DQA1*01:01 only manifests in the presence of the HLA‐DRB1*15:01 risk allele 50, 51. Several variants outside the classical regions of the MHC (both class I and class II) were also shown to be independently associated, suggesting biological functions beyond antigen display underlie the MHC risk effects.…”
Section: The Role Of the Mhcmentioning
confidence: 98%
“…There is a strong genetic contribution to MS; the human leukocyte antigen (HLA)-DRB1 locus within the major histocompatibility complex (MHC), specifically the DRB1*15:01 allele, confers the strongest risk 30 . TICS-M scores did not vary by HLA-DRB1*15:01 carrier status in MS cases; no association was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association and candidate gene studies have suggested that the greatest effects on MS risk conferred by the DR15 haplotype are driven by the HLA-DRB1*15:01 allele (5,6,41,42). However, linkage disequilibrium in the HLA-class II region makes it difficult without functional studies to distinguish whether the functionally relevant effect on MS derives only from the DRB1*15:01 or also from the neighboring genes in the HLA-DR15 region, from their combination, or from their epistatic interaction.…”
Section: Discussionmentioning
confidence: 99%